In Vitro Interactions of Antifungal Agents and Everolimus Against Aspergillus Species - Jiang, Huiping; Xiong, Jianqun; Tan, Lihua; Jin, Ping; Sun, Yi; Yang, Lianjuan; Tan, Jingwen (Frontiers in Cellular and Infection Microbiology, 2022)
Multiple cellular activities, including protein and lipid synthesis, ribosome biogenesis, and metabolic processes, are regulated by the target of rapamycin (TOR) pathway. Recent research suggests that the TOR might play an important role in various physiological functions of pathogenic fungi, such as nutrient sensing, stress response, and cell cycle progression. Given their robust immunosuppressant and antitumor activities, TOR inhibitors are widely used in clinical settings. In the present study, a microdilution checkerboard-based approach was employed to assess the interactions between the oral mammalian target of rapamycin (mTOR) inhibitor everolimus (EVL) and antifungal agents in the treatment of Aspergillus species derived from 35 clinical isolates in vitro. The results revealed that EVL exhibited promising inhibitory synergy with itraconazole (ITC), posaconazole (POS), and amphotericin B (AMB) for 85.7%, 74.2%, and 71.4%, respectively. In contrast, EVL exhibited minimal synergistic inhibitory activity (14.3%) when applied in combination with voriconazole (VRC). Antagonistic interactions were not observed. In vivo experiments conducted in Galleria mellonella revealed that EVL in combination with antifungal agents improved the larva survival rates in the ITC, VRC, POS, and AMB groups by 18.3%, 13.3%, 26.7%, and 13.3%, respectively. These data suggest that the combination treatment with antifungal agents and antifungal agents holds promise as a means of alleviating clinical aspergillosis.